Answer:
[tex]\dfrac{8x^{4}}{20}+\dfrac{3x^{2}}{2}-\dfrac{4}{5}x+C[/tex]
Step-by-step explanation:
Given the function: [tex]f(x)=\dfrac{8x^3}{5}+3x-\dfrac{4}{5}[/tex]
To take the antiderivative (or integral) of a function, we follow the format below.
[tex]f(x)=x^n\\$Then its antiderivative\\Antiderivative of f(x)$=\dfrac{x^{n+1}}{n+1}[/tex]
Therefore, the antiderivative of f(x) is:
[tex]=\dfrac{8x^{3+1}}{5(3+1)}+\dfrac{3x^{1+1}}{2}-\dfrac{4}{5}x+C\\=\dfrac{8x^{4}}{20}+\dfrac{3x^{2}}{2}-\dfrac{4}{5}x+C[/tex]
We want to check our result by differentiation.
[tex]\dfrac{d}{dx}\left(\dfrac{8x^{4}}{20}+\dfrac{3x^{2}}{2}-\dfrac{4}{5}x+C\right)\\=\dfrac{d}{dx}\left(\dfrac{8x^{4}}{20}\right)+\dfrac{d}{dx}\left(\dfrac{3x^{2}}{2}\right)-\dfrac{d}{dx}\left(\dfrac{4}{5}x\right)+\dfrac{d}{dx}\left(C\right)\\\\=\dfrac{32x^{3}}{20}+\dfrac{6x}{2}-\dfrac{4}{5}+0\\\\=\dfrac{8x^{3}}{5}+3x-\dfrac{4}{5}[/tex]